Contextualisation of Mustahik Priority Scale Criteria in LAZISNU East Java Maqasid Syariah Index Perspective - Najah, Ahmadun (Management of Zakat and Waqf Journal (MAZAWA), 2024)
This research compiles a pattern of determining the priority of mustahik or zakat recipients applied in the East Java Nahdhatul Ulama zakat institution using indicators from the maqasid syariah index. The meaning of the mustahik priority scale is still multi-interpreted, there is no standardised measure and standard set. As a result, in some areas there are mustahiks who do not receive zakat distribution, and on the other hand, one mustahik gets assistance by two zakat institutions. Another crucial problem is the inequality of recipients of zakat funds that are uneven and not need-based. This is where there needs to be a standard concept, as practised by Lazisnu East Java. This research is qualitative in nature by taking primary data from interviews with amil zakat and mustahik as recipients of zakat. The research findings show that basically the determination of mustahik in Lazisnu East Java is based on the provisions of the Qur'an. Only in the asnaf fii sabilillah is interpreted with students, teaching staff and those who seek knowledge and preach Islam. The priority scale of the eight asnaf is determined based on the needs of the asnaf for zakat assistance both consumptively and productively. The basis of needs is based on the territoriality of the asnaf, not across regions. However, in the productive aspect, the most prioritised asnaf are asnaf who can develop zakat funds. In the perspective of maqasid sharia index, the basis of need in determining the priority scale is in accordance with the sharia hierarchy that prioritises dhururi, rather than tahsiniyah